Bioresorbable Vascular Scaffold (ABSORB BVS); first report in Egyptian patients with 6 month angiographic/IVUS follow up - Hazem Khamis; Khalid Shokry; Ahmed Ramzy; Ahmed Samir (The Egyptian Heart Journal, 2014)
Objective: To evaluate the feasibility, efficacy, and safety of the ABSORB BVS (Bioresorbable Vascular Scaffold) for the treatment of de novo native coronary artery stenosis. Methods: Thirty patients with ischemic heart disease were selected between September 2012 and December 2012 and received ABSORB BVS for the treatment of de novo native significant coronary artery stenosis. Patients were followed up for six months after the procedure. In each patient, the treated segment and the periscaffold segments (5 mm proximal and distal to the scaffold edge) were analyzed by Quantitative coronary angiography (QCA) and phased-array intravascular ultrasound (IVUS) catheters in paired matched angiographic views after the procedure and at follow-up. The major clinical end point was ischemia-driven major adverse cardiac events (ID-MACE) defined as a composite of cardiac death, myocardial infarction or ischemia-driven target lesion revascularization. Results: Overall the scaffold area remained unchanged. The angiographic late lumen loss amounted to 0.27 ± 0.32 mm with an IVUS relative decrease in minimal lumen area of 1.94% (p = 0.12), without significant changes in the mean lumen area. After 2 weeks, 1 patient presented with STEMI, control coronary angiography revealed a patent stent with thrombus distal to it that was treated with a metallic drug-eluting stent (Xience V). There were no cardiac deaths or ischemia-driven target lesion revascularizations. At six months the hierarchical ID-MACE was 3.3%. Conclusions: ABSORB BVS seems an attractive option for the treatment of significant de novo native coronary artery stenosis with low risk of serious adverse events.